(untitled) (Scientific journal of the Fergana State University, 2023)
The article aims to determine whether the types of folk proverbs related to human health are indeed reflected in medicine, as their meaning is relevant to health preservation as well as linguocultural specificity. Proverbs are studied and interpreted using linguistic explanatory dictionaries as well as medical resources. The research has shown that proverbs are a sample of folk wisdom tested over the years and do have practical significance in medicine. Also, the influence of folk customs, culture on proverbs and sayings is revealed. In conclusion, it can be said that folk proverbs are based on medicine, and the application of some of them globally and some of them locally will be of great importance to improve people’s medical literacy.